Physician and Pharmacist Understanding of the Risk of Urinary Retention with Retigabine (Ezogabine): A REMS Assessment Survey - Ishihara, Lianna; Beck, Melissa; Travis, Sara; Akintayo, Olusegun; Brickel, Neil (Drugs - real world outcomes, 2015)
Background The Risk Evaluation and Mitigation Strategy (REMS) for retigabine/ezogabine (RTG/EZG) required an evaluation of the effectiveness of the communication plan to communicate about the risks with use of RTG/EZG. Objective GlaxoSmithKline conducted a survey to assess understanding of the risk of urinary retention (UR) with RTG/EZG and to evaluate the effectiveness of the communication plan. Methods This was a US-based, cross-sectional, non-interventional, observational survey, conducted from February to April 2013, of physicians who had prescribed RTG/EZG in the past year, and pharmacists who had dispensed an antiepileptic drug within the past 3 months. Thirteen primary objective questions (five specific to UR risk) were included in the survey, which assessed healthcare professionals’ (HCPs’) understanding of UR risk and symptoms of acute UR associated with RTG/EZG. The primary outcome was the proportion of HCPs correctly answering each question. For each question, a proportion of correct responses ≥80 % was considered to represent sufficient understanding of associated risks. Results Of 1028 HCPs screened, 373 participated. Six of 13 questions (3/5 specific to UR risk) met the ≥80 % threshold for correct responses in the physician cohort. No questions achieved this threshold in the total pharmacist group; however, four questions scored ≥80 % when stratified by pharmacists who had dispensed RTG/EZG. Conclusions Results demonstrated a mixed level of understanding of aspects of UR risk associated with RTG/EZG, although some risk questions did not meet the 80 % threshold, especially among pharmacists. This is likely to have been due to the short time that RTG/EZG has been available and its limited use. This study provides the first evaluation of the REMS communication plan on the risk of UR with RTG/EZG.